Pengaruh Lingkungan Kerja, Kesehatan Kerja, Keselamatan Kerja Terhadap Produktivitas Karyawan (Studi Kasus PT. Optima Sinergi Convestama Kota Semarang) - Aprilia, Rosa; Kartika, Erawati; Nathanael, Suhaji (Jurnal Ilmiah Aset, 2024)
This research aims to examine the influence of the work environment, work health and work safety on employee productivity at PT. Optima Sinergi Convestama Semarang City. This type of research is explanatory research. The sampling technique was a census and data collection through distributing questionnaires and interviews with 125 respondents. The data analysis method used is multiple linear regression with SPSS 23. The F Test results in the research found that the work environment, work health and work safety have a significant effect on employee productivity at PT. Optima Sinergi Convestama Semarang City. This means that improving working environmental conditions, occupational health and occupational safety also has an impact on improving employee productivity conditions, and vice versa. The results of the calculation of the coefficient of determination value were obtained at 0.720, which means that the influence of the work environment, work health and work safety on employee productivity is 7.20%. In conclusion, the work environment, work health and work safety have a positive and significant effect on the productivity of PT Optima Sinergi Convestama Semarang City.